Isolation, Screening and Identification of Cellulolytic Streptomyces corchorusii (Mn244066) From Soil Sample of Visakhapatnam: Life Sciences-Microbiology for health care - L.Sujatha; K.P.J. Hemalatha (International Journal of Life Science and Pharma Research, 2022)
Fifty one isolates of cellulolytic bacteria were isolated from cow dung and two soil samples were obtained from Kambalakonda Wildlife Sanctuary and RCD Biodiversity Park in Visakhapatnam, Andhra Pradesh by Enrichment method in basal salt medium with cellulose as substrate for degradation. The cellulolytic activity of the isolated bacteria was determined by the diameter of the zone of hydrolysis by Gram’s iodine dye staining method. After primary screening, a total of fifty one isolates showed cellulolytic activity. Out of fifty one strains of cellulolytic bacteria, twenty three isolates from Kambalakonda Wildlife Sanctuary, seventeen isolates from RCD Biodiversity Park and Eleven isolates from cow dung sample obtained from cattle ranch, Visakhapatnam showed cellulase activity. Seven strains showed maximum hydrolytic value greater than 4.0 cm, nineteen strains showed average hydrolytic value between 3.0 and 3.9 cm and twenty one strains showed minimum hydrolytic value between 1.5 and2.9 cm. The potential isolates were obtained from Kambalakonda Wildlife Sanctuary and RCD Biodiversity Park than cow dung sample. The 13 C strain exhibited maximum hydrolytic value of 5.6 cm which was designated as KKV1. The strain KKVI was identified as Streptomyces corchorusii (MN244066) by morphological, cultural, biochemical and 16S rRNA sequence. The CMCase and FPase activity of the crude sample were examined by DNS method and found to be 0.21 U/ml and 0.041 U/ml respectively and the specific activity was 4.38 U/mg proteins and 0.86 U/mg proteins respectively. The present study emphasizes that the Streptomyces corchorusii have a higher cellulase activity and the soils of bio reserves have a lot of scope for isolating high cellulolytic bacteria which can be exploited for different industrial purposes.